Comparative aspects of the reproductive biology of seabreams (Pisces: Sparidae) - Garratt, Patrick Ashworth (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1994)
Sexuality in seabreams (Sparidae) is considered to be more complex than in any other family of fishes. Early work indicated five reproductive styles within the family: protandry, protogyny, simultaneous hermaphroditism, rudimentary hermaphroditism and gonochorism. More recently two reproductive styles have been suggested: sex change (protandry and protogyny) and secondary gonochorism (rudimentary hermaphrodites). The need for detailed descriptions of sex differentiation, gonad development and spawning behaviour in this family has been identified by a number of workers in this field. The aims of the present study were: i) to provide accurate, detailed descriptions and comparisons of gonadal development in representatives of each reproductive style, ii) to investigate their spawning strategies, and iii) to relate these findings to current theories on hermaphroditism and sex change in fishes. Four species were investigated. Slinger, Chrysoblephus puniceus, the only known protogynous hermaphrodite in Natal. Santer, Cheimerius nufar, described in the literature as a rudimentary hermaphrodite. Riverbream, Acanthopagrus berda suspected to be a protandrous hermaphrodite. Natal stump nose, Rhabdosargus sarba, reported elsewhere as a protandrous hermaphrodite. Detailed histological analysis showed that morphological and cytological development of all gonads proceeded initially in a female direction, irrespective of reproductive style, but that differentiating gonads of protandrous and protogynous hermaphrodites could easily be distinguished from one another. Early gonadal development was similar in R. sarba and A. berda with gonadal primordia differentiating into distinctly bisexual organs. In C. puniceus and C. nufar gonadal primordia differentiated into ovaries with reduced, inert male elements in the tunica albuginea. Sex differentiation occurred relatively late (100-150mm fork length) in all the species investigated. Few cells conforming to primordial germ cells (PGC's) described in other teleosts were identified. These cells only became evident after the appearance of gonial cells and their identity is questioned. Gonial cells appeared to develop within less-electron-dense cysts of cells. Gonial cells in presumptive male and female elements could not be distinguished from one another morphologically, suggesting the bipotentiality of these cells. All R. sarba and A. berda gonads pass through a predominantly male phase and all fish function first as males, indicating protandrous sex change in both species. All C. puniceus and C. nufar gonads develop initially into ovaries. Sex change thus occurs in both species and protogyny in C. puniceus is confirmed. In C. nufar, sex change may occur before or after sexual maturity and its reproductive style remains uncertain. Investigations into the spawning habits of A. berda have shown that this species spawns inside the Kosi estuary at night. Eggs are released during peak ebb tides. Spawning occurs in large aggregations and several to many males compete to spawn with individual females. This spawning strategy does not conform to predictions made from the size advantage model for protandrous species. Chrysoblephus puniceus appears to have preferential spawning sites on down-current outer reef margins. Spawning was not observed in this species, but changes in behaviour, social structure and colour during the spawning season suggest that it may have a mating system similar to several protogynous labrids and scarids, in which territories are temporary. Cheimerius nufar has a similar mating system. Temporary territories are established by large males during the spawning season, which extends from August to November. Mating is by pair-spawning and dominant territorial males obtain a disproportionate number of matings. 'Streaking' appears to represent an alternative mating strategy for males until they attain a sufficient size to establish and defend territories. The mating pattern of C. nufar suggests that it is either a gonochorist which does not conform to current theoretical predictions; or that it is a protogynous hermaphrodite incorrectly diagnosed as a rudimentary hermaphrodite; or that protogyny in the Sparidae is an ancestral condition and C. nufar is in the process of evolutionary change from a protogynous to a gonochoristic form (or visa versa).
Keywords: Sparidae -- Physiology Sparidae -- Reproduction